2001
DOI: 10.1146/annurev.pharmtox.41.1.367
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Responses to DNA Damage

Abstract: Cells are constantly under threat from the cytotoxic and mutagenic effects of DNA damaging agents. These agents can either be exogenous or formed within cells. Environmental DNA-damaging agents include UV light and ionizing radiation, as well as a variety of chemicals encountered in foodstuffs, or as air- and water-borne agents. Endogenous damaging agents include methylating species and the reactive oxygen species that arise during respiration. Although diverse responses are elicited in cells following DNA dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
293
1
15

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(326 citation statements)
references
References 210 publications
5
293
1
15
Order By: Relevance
“…DNA damage includes abnormalities such as single and double strand breaks, 8-hydroxydeoxyguanosine residues and DNA adducts. 23,24 The present results revealed that SK228 could cause DNA damage by binding to the minor groove of DNA, intercalating into DNA and increasing ROS production. However, the binding effects are not strong at lower concentrations.…”
Section: Discussionmentioning
confidence: 56%
“…DNA damage includes abnormalities such as single and double strand breaks, 8-hydroxydeoxyguanosine residues and DNA adducts. 23,24 The present results revealed that SK228 could cause DNA damage by binding to the minor groove of DNA, intercalating into DNA and increasing ROS production. However, the binding effects are not strong at lower concentrations.…”
Section: Discussionmentioning
confidence: 56%
“…These DSBs are induced by endogenous and exogenous factors, including exposure to ionizing radiation (IR) and radiomimetic drugs, collapse of replication forks and programmed cleavage by specific endonucleases during meiotic recombination and V(D)J recombination. [12][13][14][15] DSBs are potent triggers of cell cycle arrest and apoptosis. 14,16 The effective and accurate regulation of DNA DSB repairs is essential for genomic integrity.…”
mentioning
confidence: 99%
“…[12][13][14][15] DSBs are potent triggers of cell cycle arrest and apoptosis. 14,16 The effective and accurate regulation of DNA DSB repairs is essential for genomic integrity. Double strand breaks are especially dangerous during S phase when single stranded DNA molecules are processed.…”
mentioning
confidence: 99%
“…A sperm becomes positively charged when it completely loses the negatively charged glycoproteins anchored/adhered on its membrane. It is well known that apoptosis is a mechanism to eliminate dysfunctional cells [52]. During apoptosis in sperm, the integrity of the membrane is lost due to the translocation of phosphatidylserine [53], during which the phosphatidylserine is shifted from the interior to the exterior of the plasma membrane [54,55].…”
Section: Discussionmentioning
confidence: 99%